A Study on the Significance of Customer Relationship In Hotel Industry: Exploring the Impact of Relationship Marketing in the Hotel Industry (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The study investigatesthe relationshipmarketing(RM) strategy of Hotel industry and examines whether after the implementation-customer relationships were strengthened through perceived improvements in the Hotel industry and consequently loyalty towards the Hotel.